DESIGN AND DEVELOPMENT OF SIGHT-READING APPLICATION FOR KIDS - Trianggoro Wiradinata, Christina Theodora Loman , (PROCEEDING IC-ITECHS 2014, 2014)
The most common problem faced by kids is the difficulty to sight-read a music score.On the other side, nowadays kids love to learn by playing games in the form of mobile applications. Unfortunately, currently available mobile-based music games tend to target adults, hence not so appealing and therefore more difficult to learn. Considering the difference between every childrenâs ability, this application is using Fisher-Yates Shuffle algorithm for problem shuffling in each level and also the principal of decision tree for problem choosing based on the problemâs weight and childrenâs ability. As a solution to the problem stated above, this study is conducted by the design of âAdventure in Music Landâ, an Android-based music theory education app specifically designed for kids aged 9 â 13. This application is being used to help kids improve their sight-reading ability.